2016
DOI: 10.1177/2055102916634361
|View full text |Cite
|
Sign up to set email alerts
|

Integrating intervention targets offered by homeostatic theory

Abstract: Marks presents “homeostatic theory” which proposes that weight gain is fostered by a “Circle of Discontent” consisting of body dissatisfaction, negative affect, and overconsumption. This innovative framework offers potential intervention approaches, including victim-blaming, stigma, and discrimination, as well as devalorizing the thin-ideal. Our article discusses possible ways that clinical health psychologists based in university settings may be uniquely positioned to consider and implement large-scale progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Homeostasis theory proposes that weight gain is fostered by a COD consisting of body dissatisfaction, negative affect and overconsumption. Drawing on this framework, Annunziato and Grossman (2016) describe research in two domains, victim blaming and devalorizing the thin ideal. They suggest that university-based clinical health psychologists are uniquely positioned to implement large-scale approaches that have shown promise in addressing core issues in the HTO.…”
Section: Issues Requiring More Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Homeostasis theory proposes that weight gain is fostered by a COD consisting of body dissatisfaction, negative affect and overconsumption. Drawing on this framework, Annunziato and Grossman (2016) describe research in two domains, victim blaming and devalorizing the thin ideal. They suggest that university-based clinical health psychologists are uniquely positioned to implement large-scale approaches that have shown promise in addressing core issues in the HTO.…”
Section: Issues Requiring More Researchmentioning
confidence: 99%
“…Annunziato and Grossman cite examples of research that include a ‘Social and Emotional Learning’ curriculum in Sweden that demonstrated decreases in victimization (Kimber et al, 2008) and the ‘Body Project’ which produced reductions in eating disorders (Stice et al, 2013), in thin-ideal internalization, body image dissatisfaction and negative affect in female students (Stice et al, 2011) and an Internet-based programme that demonstrated large weight gain prevention effects (Stice et al, 2014). Annunziato and Grossman (2016) propose more extensive use of both systemic and individual interventions with adolescents and young adults in school settings. For example, large-scale programmes in secondary schools and universities could be designed to bring about culture change.…”
Section: Issues Requiring More Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…'Principle I (Agency)' states: 'The voluntary behaviour of conscious organisms is guided by a universal striving for equilibrium, a striving with purpose, desire and intentionality' (Marks, 2018: 11). 'Psychological homeostasis' is specified as the equivalent of physiological homeostasis described by Bernard and Cannon. As already mentioned, the theory was first proposed as a theory of obesity (Annunziato and Grossman, 2016;DiClemente and Delahanty, 2016;Marks, 2015). Several empirical studies and reviews have supported the obesity theory, for example, Jumbe et al ( 2017 The inverted-U shaped curve is of particular relevance to this theory of well-being because a Gaussian, inverted U-shaped curve can be guaranteed to be the product of any homeostatic system (Chrousos, 2009), which I discuss next.…”
Section: The Origin Of the Theorymentioning
confidence: 96%
“…One early application of the GTB was an effort to explain the causes of obesity (Annunziato and Grossman, 2016;DiClemente and Delahanty, 2016;Marks, 2015Marks, , 2016. Czepczor-Bernat et al (2020) provide an empirical verification of the theory with their study of restrained and uncontrolled eating among children and adolescents.…”
Section: The General Theory Of Behaviourmentioning
confidence: 99%